Impact of control interventions on lung alveolarization and the lung transcriptome during postnatal lung development of mice - Fehl, Joshua; Justus Liebig University Giessen (My University, 2022)
Studies on normal and aberrant lung alveolarization—particularly in the context of bronchopulmonary dysplasia—often employ animal models to investigate molecular processes of lung development. To this end, pharmacological agents can be applied via the intraperitoneal route to modulate biochemical pathways or to regulate gene expression in transgenic animals. Such studies typically include control interventions, where seemingly inert agents are administered; thereby establishing a point of reference for the analysis of the partner experiment. However, the effects of control interventions on the lung development of the laboratory mouse are largely unknown to date. Therefore, the impact of frequently deployed control interventions on lung alveolarization and the lung transcriptome during postnatal lung development of C57Bl/6J mice was examined in this dissertation. Alveolarization was assessed by design-based stereology, whereas an RNA-Seq screen with subsequent real-time RT-PCR validation was utilized to detect transcriptomic changes. The following effects were found: parenteral administration of scrambled microRNA inhibitors (called antimiR) impacted lung volume, septal thickness, and the transcriptome of developing mouse lungs; with some effect dependent upon the nucleotide sequence of the antmiRs. Daily injections of isotonic saline altered lung volume, whereas the effect on the transcriptome was limited. Parenteral administration of Miglyol (a solvent vehicle of tamoxifen) accelerated the growth of mouse pups and changed the abundance of 74 mRNA transcripts in the lung. Tamoxifen led—in the absence of Cre recombinase—to a reduced growth of experimental animals, a decreased lung volume and an impairment of alveolarization. Furthermore, the application of tamoxifen altered the abundance of a broad spectrum of mRNA transcripts in the lung. In sum, the data of this thesis demonstrate that widely applied control interventions in studies on lung development may directly impact lung alveolarization and the lung transcriptome.
Einfluss von Kontrollinterventionen auf die Alveolarisierung und das Transkriptom der postnatalen Lungenentwicklung bei Mäusen
Keywords: alveolarization; antimiR; lung development; tamoxifen; miglyol; RNA-Seq; stereology; ddc:610